2005
DOI: 10.1101/lm.5905
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor-dependent processes in the medial prefrontal cortex are important for acquisition and the early stage of consolidation during trace, but not delay eyeblink conditioning

Abstract: Permanent lesions in the medial prefrontal cortex (mPFC) affect acquisition of conditioned responses (CRs) during trace eyeblink conditioning and retention of remotely acquired CRs. To clarify further roles of the mPFC in this type of learning, we investigated the participation of the mPFC in mnemonic processes both during and after daily conditioning using local microinfusion of the GABA A receptor agonist muscimol or the NMDA receptor antagonist APV into the rat mPFC. Muscimol infusions into the mPFC before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 46 publications
7
67
0
Order By: Relevance
“…The mPFC involvement in trace and contextual fear conditioning following long retention intervals is consistent with recent observations (Takehara-Nishiuchi et al 2005. Bontempi et al (1999) showed that retention of a spatial discrimination is associated with elevated metabolic activity in the DH 5 d following acquisition, whereas activity in this region 25 d following acquisition is significantly attenuated; frontal cortical activity showed an opposite pattern.…”
Section: Discussionsupporting
confidence: 78%
“…The mPFC involvement in trace and contextual fear conditioning following long retention intervals is consistent with recent observations (Takehara-Nishiuchi et al 2005. Bontempi et al (1999) showed that retention of a spatial discrimination is associated with elevated metabolic activity in the DH 5 d following acquisition, whereas activity in this region 25 d following acquisition is significantly attenuated; frontal cortical activity showed an opposite pattern.…”
Section: Discussionsupporting
confidence: 78%
“…(2) Although we chronically infused D-APV to affect systems consolidation, there exists the possibility that interference with cellular consolidation, rather than systems consolidation, caused the impairments we observed in the present experiment. However, the fact that the involvement of NMDA receptors in the mPFC in cellular consolidation is limited to the time when a memory is beginning to be formed (Takehara-Nishiuchi et al, 2005) leads us to reject this possibility. Therefore, the present results suggest that neural processes in the mPFC are required for systems consolidation.…”
Section: Chronic Infusion Of D-apv Attenuated Nmda Receptordependent mentioning
confidence: 96%
“…Theoretical models (Hasselmo et al, 2000;Hasselmo and Stern, 2006) have related this function of the entorhinal cortex to its self-sustaining spike activity observed in vitro (Egorov et al, 2002;Tahvildari et al, 2007) and persistent activity during a delay period following stimulus presentation in vivo (Suzuki et al, 1997;Young et al, 1997). Although persistent activity can be observed in both the LEC and MEC (Egorov et al, 2002;Tahvildari et al, 2007), the LEC is more strongly connected with the perirhinal cortex, whose projections mediate highly processed sensory information (Furtak et al, 2007), and with the prelimbic medial prefrontal cortex (Hoover and Vertes, 2007;Agster and Burwell, 2009), which plays a critical role in memory retrieval in trace eyeblink conditioning (Takehara-Nishiuchi et al, 2005;Oswald et al, 2010). Furthermore, these two regions show differential selectivity for spatial versus nonspatial information (Hargreaves et al, 2005).…”
Section: Discussionmentioning
confidence: 99%